The Economic Impact of High Consequence Zoonotic Pathogens: Why Preparing for these is a Wicked Problem - Miller, Gay Y.; Parent, Katie (Journal of Reviews on Global Economics, 2012)
Abstract: This paper reviews literature on the economic impacts of outbreaks and control strategies for high consequence zoonotic priority diseases, ie. zoonotic diseases that are generally FADs, zoonotic diseases that occur rarely, or zoonotic diseases that have bioterrorist potential sufficient to be important for the United States. Such diseases are referred to here as zoonotic priority diseases (ZPDs). These ZPDs are categorized into three levels of economic impact: high, moderate, and low with the recognition that there are aspects of each of these diseases that could make the categorization presented here inaccurate. Arguments are made for why determination of optimal ZPD and more generally FAD preparedness and response strategies are wicked problems. The paper concludes with the implications for further development of appropriate ZPD policy and some needs for further analyses.